2022
DOI: 10.1038/s41467-022-29377-3
|View full text |Cite
|
Sign up to set email alerts
|

RNA aptamers specific for transmembrane p24 trafficking protein 6 and Clusterin for the targeted delivery of imaging reagents and RNA therapeutics to human β cells

Abstract: The ability to detect and target β cells in vivo can substantially refine how diabetes is studied and treated. However, the lack of specific probes still hampers a precise characterization of human β cell mass and the delivery of therapeutics in clinical settings. Here, we report the identification of two RNA aptamers that specifically and selectively recognize mouse and human β cells. The putative targets of the two aptamers are transmembrane p24 trafficking protein 6 (TMED6) and clusterin (CLUS). When given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…With the help of gene editing technology, it may also be possible to use gene therapy to restore the expression of abnormal ncRNAs in patients in the long term ( 170 ). A recent study developed a tool for RNA delivery that targets β-cells ( 171 ). In addition, various carriers, including liposomes and exosomes, have been found to be useful for delivering RNA ( 172 , 173 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the help of gene editing technology, it may also be possible to use gene therapy to restore the expression of abnormal ncRNAs in patients in the long term ( 170 ). A recent study developed a tool for RNA delivery that targets β-cells ( 171 ). In addition, various carriers, including liposomes and exosomes, have been found to be useful for delivering RNA ( 172 , 173 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current absence of specific probes hinders our ability to accurately measure the mass of human β cells and deliver effective treatments in clinical settings. Van et al have documented the discovery of two RNA aptamers, which selectively and specifically recognize mouse and human β cells by targeting transmembrane p24 trafficking protein 6 and clusterin [ 86 ]. Multiple investigations have showcased the effectiveness of utilizing exosomes, which have emerged as highly promising nano-carriers for delivering therapeutic agents like small interfering RNA, microRNAs, proteins, or chemical medicines to targeted cells [ 87 , 88 ].…”
Section: Rational Design Strategiesmentioning
confidence: 99%
“…Their distribution can be influenced by factors like blood flow, tissue permeability, and interactions with proteins or cells in the circulation [ 186 ]. Nanozymes can accumulate in specific tissues or organs, depending on their targeting strategies or the physiological characteristics of the target site [ 61 , 86 ]. Once inside the cell, nanozymes can be localized in different cellular compartments, such as endosomes, lysosomes, or cytoplasm, depending on the specific targeting or delivery strategy employed [ 104 ].…”
Section: The Pharmacokinetic Characteristics Of Nanozymesmentioning
confidence: 99%
“…In 2022, Van Simaeys et al reported the identification of two RNA aptamers that could bind to transmembrane p24 trafficking protein 6 and clusterin of mouse and human β cells. Similar to the design shown in Figure , aptamers 1-717 and 12-3773 were conjugated with XIAP saRNA to specifically mediate the expression of inflammatory cytokines, improving the efficacy of human islet transplantation in mice with immunodeficiency …”
Section: Aptamer-based Sarna Targeted Deliverymentioning
confidence: 99%
“…In 2006, a small activating RNA (saRNA) was designed to activate gene transcription, emerging as a powerful tool for targeting various human cancers. , The C/EBPα (CCAAT/enhancer-binding-protein-alpha), , DPYSL3 (dihydropyrimidinase-related protein 3), and XIAP (X-linked inhibitor of apoptosis protein) genes have been investigated as targets by aptamer–saRNA chimeras for the targeted treatment of pancreatic cancer. Based on cell-SELEX technology, Yoon et al selected aptamers able to bind specifically to surface epitopes of human pancreatic adenocarcinoma, PANC-1.…”
Section: Aptamer-based Sarna Targeted Deliverymentioning
confidence: 99%